VARIACIÓN INTRAESPECÍFICA DEL TAMAÑO DE ADULTOS DE CULICIDAE (DIPTERA) EN EL ÁREA PLATENSE, PROVINCIA DE BUENOS AIRES, ARGENTINA - Macía, Arnaldo (Acta Entomológica Chilena, 2022)
Body size may be strongly related to physiological status and reproductive success in insects. Intraspecific size variations in Aedes albifasciatus Macquart, Aedes crínifer (Theobald), Culex dolosus Lynch Arribál/aga, Culexpipiens L. and Psorophoraferox Humboldt females, were quantified in order to test the hypothesis that increased body size is related to increased parity in field populations of these mosquitoes. Host-seeking adults were collected every fifteen days in Punta Lara and La Plata, Buenos Aires, Argentina, with C.D.C. traps from September 1990 to August 1991. Wing lenght was measured in all mosquitoes. Physiological status was determined according to ovarían tracheation. Size variation was high, and the seasonality of mean wing lenght showed an inverse relationship with temperature. No evidence of increased reproductive success in larger individuáis was found. Therefore, it was unable to demónstrate that large-bodied females of the species have increased fitness than small ones.